Understanding towards diabetes mellitus among rural adult community in Malaysia - Minhat, Halimatus Sakdiah; Hamedon, Titi Rahmawati (IDOSI Publications, 2014)
Diabetes mellitus (DM) has shown an increasing trend globally and a growing burden of DM in Malaysia. This study aimed to explore the understanding of the rural adult community in Malaysia on DM. A cross-sectional study was conducted involving adult residents aged 18 years old and above, living in two separate villages in the district of Kuala Pilah, Negeri Sembilan. A pre-tested questionnaire was used for data collection using a face-to-face interview to ensure the accuracy and to avoid incompleteness of information given. Respondents’ understanding on DM was reflected by their knowledge, which was measured using a 3-point likert scale questionnaire consisted of 13 items. A total of 234 respondents consented for the study with mean age of 45.54 ± 17.61 years old. Majority were 45 years old and younger (56.8%), females (59.0%), had higher education level (76.9%), had individual monthly income of RM1500 and less (79.5%) and were not suffering from diabetes mellitus (81.2%). The median score for knowledge related to diabetes mellitus was 20.00 (IQR = 7), with 58.1% had a poor score below the median value. Only diabetic status was significantly determining understanding of the respondents on diabetes mellitus. The findings of the study indicated that majority of the rural community adult involved in the study had a remarkably low knowledge related to diabetes mellitus which was significantly related to their diabetic status. The existing health promotion programs could possibly limited among those already suffered from diabetes, which indicate the needs for a more extensive community-based education in order to reduce the prevalence of diabetes in the community.